Decentralized Network Governance: Blockchain Technology and the Future of Regulation - Zwitter, Andrej; Hazenberg, Jilles (Frontiers in Blockchain, 2020)
Advancements in the digital domain, for example in blockchain technology, big data and machine learning, are increasingly shaping the lives of individuals, groups, organizations, and societies. These developments call for effective governance to protect the basic interests and needs of these actors. Simultaneously, the very nature of governance is also changing. Policy-making is increasingly moving away from top-down governance by the state towards more horizontal modes of governance. This paper reviews the literature on governance theory in order to conceptualize governance as a mode of decentralized, networked regulation. We argue that the current dominant modes of governance are inadequate in understanding governance in the digital domain, and are poorly equipped to conceptualize novel forms of governance such as decentralized autonomous organizations (DAOs). Therefore, this study proposes a new mode of governance based on the regulation of new power relationships between the state and actors in the digital domain. This model further explores the role that blockchain technology can play in what we term decentralized network governance.